Role of multiple endocrine neoplasia type 1 mutational analysis in clinical practice. - Newey, P; Thakker, R (2011)
OBJECTIVE: To review and assess the role of MEN1 mutational analysis in clinical practice. METHODS: Articles relevant to MEN1 mutation testing and screening were reviewed. RESULTS: Multiple endocrine neoplasia type 1 (MEN 1) is an autosomal dominant disorder characterized by the combined occurrence of tumors of the parathyroid glands, pancreatic islet cells, and anterior pituitary gland. MEN 1 is associated with premature mortality attributable primarily to malignant pancreatic neuroendocrine tumors and foregut carcinoids. The MEN1 gene is located on chromosome 11q13, and germline MEN1 mutations are highly penetrant and lead to tumor development in >99% of patients by the age of 45 years. Current consensus guidelines recommend an integrated program of mutational analysis of the MEN1 gene and a combination of biochemical and radiologic screening to detect the early development of tumors and thereby reduce the morbidity and mortality associated with MEN 1. Our results reveal that MEN1 mutational analysis helps to confirm the clinical diagnosis, identify asymptomatic family members who have a MEN1 mutation and require screening from an early age, and identify the 50% of family members who do not have the MEN1 mutation and can therefore have the burden of screening and anxiety regarding potential disease removed. Moreover, MEN1 mutational analysis helps to resolve diagnostic challenges due to phenocopies, which occur in 5% to 10% of families with MEN 1. CONCLUSION: MEN1 mutational analysis facilitates clinical management and provides benefits to patients and families with MEN 1.